Transport phenomena in porous media : aspects of micro/macro behaviour - Ichikawa, Yasuaki (Springer Berlin Heidelberg, 2012)
This monograph presents an integrated perspective of the wide range of phenomena and processes applicable to the study of transport of species in porous materials. In order to formulate the entire range of porous media and their uses, this book gives the basics of continuum mechanics, thermodynamics, seepage and consolidation and diffusion, including multiscale homogenization methods. The particular structure of the book has been chosen because it is essential to be aware of the true properties of porous materials particularly in terms of nano, micro and macro mechanisms.  This book is of pedagogical and practical importance to the fields covered by civil, environmental, nuclear and petroleum engineering and also in chemical physics and geophysics as it relates to radioactive waste disposal, geotechnical engineering, mining and petroleum engineering and chemical engineering.